Impact of Conditional Cash Transfer in the Philippines: The Case of Rural Vs. Urban Beneficiaries - Charlyn, Charlyn (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
This paper analyzes the effectiveness of the CCT program in the Philippines in terms of its effect on conditionality goods as reflected by food, health, and education expenditures of households from rural and urban areas that benefitted the program. The study used secondary cross-section data and employed the Propensity Score Matching (PSM) methodology in estimating the average treatment effect on the treated. In terms of share to total expenditures, the study finds that CCT has a significant effect on education for household beneficiaries in rural areas and has improved the quality of food consumed by household beneficiaries in urban areas. Also, the study reveals a decrease in the per capita total expenditure and per capita food expenditure of the household beneficiaries in urban areas driven by their improved saving behavior. However, CCT has no significant effect on conditionality goods such as health and education for household beneficiaries in urban areas. For household beneficiaries in rural areas, only the increase in the share of education and carbohydrate foods are significant. Based on the findings of the study, the CCT program, at some point, is effective in meeting its short-term goal, but it must be more targeted in order to improve its impact on other conditionality goods.